Preparation method and application of multilayer lead-free piezoelectric ceramic piece
By adopting the sheet-layer interleaved isostatic pressing process of different components of A and B, combined with ball milling and solid phase synthesis, multi-layer lead-free piezoelectric ceramic sheets are prepared, which solves the problems of complex process, high cost and unstable performance of existing lead-free piezoelectric ceramic materials, and achieves excellent piezoelectric performance at working temperature.
Patent Information
- Application Number
- CN202411633702.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-28
AI Technical Summary
The existing lead-free piezoelectric ceramic materials have complex preparation processes, high cost, poor performance stability, and major impacts on temperature and humidity.
Multi-layer lead-free piezoelectric ceramic sheets were prepared by staggered isostatic pressing process of different components of A and B. nanopowders were prepared by ball milling to reduce the sintering temperature; KNN powders were prepared by solid-phase synthesis method to improve piezoelectric properties, and particle size growth and size regulation was performed through the second-stage high-temperature sintering process.
It realizes lead-free piezoelectric ceramic materials with simple process, low cost, stable performance and suitable for large-scale production, and has excellent piezoelectric properties at operating temperature, avoiding performance fluctuations caused by temperature and humidity changes.
Smart Images

Figure CN119528569A_ABST
Abstract
Description
Technical field:
[0001] The present invention relates to the technical field of piezoelectric ceramic material manufacturing, and in particular to a method for preparing a non-lead, environmentally friendly, multi-phase coexisting, multi-layer lead-free piezoelectric ceramic sheet having excellent piezoelectric performance within a working temperature range and its application. Background technology:
[0002] As we all know, piezoelectric ceramics are an important functional ceramic material that can generate electrical signals when subjected to mechanical stress or produce mechanical deformation under the action of an electric field. Due to its unique physical properties, piezoelectric ceramics are widely used in various high-tech fields, such as sensors, drivers, transducers, etc. Traditional piezoelectric ceramic materials are mainly based on lead-based materials, such as PZT (lead zirconate titanate). However, since lead is a toxic and harmful element that poses a threat to the environment and human health, the development of lead-free piezoelectric ceramic materials has become a hot topic in recent years. Existing lead-free piezoelectric ceramic materials mainly include KNN (sodium potassium niobate) series, BNT (sodium bismuth titanate) series, BT (barium titanate) series, etc. These materials have solved the problem of lead pollution to a certain extent, but there are still some problems and challenges. Existing lead-free piezoelectric ceramic materials still have some problems and challenges in terms of preparation process, cost, performance stability, etc. For example, although the KNN series piezoelectric ceramic material has good piezoelectric properties, its preparation process is complicated, the cost is high, and it is difficult to achieve large-scale production. At the same time, the piezoelectric properties of KNN piezoelectric ceramic materials are greatly affected by factors such as temperature and humidity, which limits their application range. Therefore, developing a lead-free piezoelectric ceramic material with simple process, low cost, stable performance and environmental friendliness is an urgent problem to be solved in the current technical field. Summary of the invention:
[0003] In view of the shortcomings and deficiencies in the prior art, the present invention proposes a method for preparing a non-lead, environmentally friendly multilayer lead-free piezoelectric ceramic sheet with reasonable process, low cost and suitable for large-scale production and application, and its application.
[0004] The present invention is achieved by the following measures:
[0005] A method for preparing a multilayer lead-free piezoelectric ceramic sheet, characterized in that it is obtained by isostatic pressing by staggered lamination of two different components of type A and type B sheets, and specifically comprises the following steps:
[0006] Step 1: Prepare type A and type B piezoelectric ceramic green bodies respectively:
[0007] Step 1-1: Weigh the piezoelectric ceramic green powder, the chemical formula of which is li x Na 0.52 K (1-x-0.52) Nb (1-y-z) Sb y Ta zO 3; , where x=4%, y=7.5%, Z=5% in A-type piezoelectric ceramic green powder, and the chemical formula is li 0.04 Na 0.5 2K 0.44 Nb 0.85 Sb 0.075 Ta 0.05 O3, B-type piezoelectric ceramic green powder contains x=6%, y=10%, Z=5%, and the chemical formula is Li 0.0 6Na 0.52 K 0.42 Nb 0.85 Sb 0.1 Ta 0.05 O3 is prepared by weighing Li2CO3, Na2CO3, K2CO3, Nb2O5, Ta2O5 and Sb2O3 respectively and mixing them, wherein sodium carbonate and potassium carbonate powders are dried and dehydrated at 300-400°C in advance;
[0008] Step 1-2: Add the weighed powders to the ball mill respectively, and add grinding balls, grinding media, and powder raw materials respectively, place the raw materials in a planetary ball mill or a nano ball mill for powder grinding, mix them thoroughly, and ball mill at 400-500rpm for 24-36 hours;
[0009] Step 1-3: The ball-milled slurry is sieved to separate the balls, the separated slurry is desolventized and dried, and the dried powder is ground and dispersed using a mortar grinder to form powder accumulation particles with uniform particle size and no agglomeration;
[0010] Step 1-4: placing the powder stacked particles in an alumina crucible and pre-sintering at 900-950° C.;
[0011] Step 1-5: The pre-sintered powder is placed in a ball mill, and plasticizer, solvent, dispersant, and PVB are added respectively. The powder is ball milled at 100-150 rpm for 18 hours using a drum ball mill. After that, the slurry is left to stand for 48 hours for full emulsification and dispersion.
[0012] Step 1-6: The emulsified and dispersed slurry is subjected to degassing treatment, and the degassing slurry is placed in a coating machine to be made into 30-50 μm thick type A piezoelectric ceramic green bodies and type B piezoelectric ceramic green bodies, respectively, and placed in a constant temperature and humidity chamber for aging;
[0013] Step 2: alternately stacking the aged type A piezoelectric ceramic green bodies and the type B piezoelectric ceramic green bodies to form stacked green bodies, and performing a 30-50 MPa lamination isostatic pressing treatment on the stacked green bodies to obtain isostatically pressed green bodies;
[0014] Step 3: placing the isostatically pressed green block in a high-temperature sintering furnace for sintering;
[0015] Step 4: The sintered piezoelectric ceramics are polarized to obtain a multi-layer lead-free piezoelectric ceramic sheet.
[0016] The present invention also proposes an application of the above-mentioned multi-layer lead-free piezoelectric ceramic sheet, characterized in that it also includes preparing a piezoelectric ceramic driving component using the multi-layer lead-free piezoelectric ceramic sheet, specifically, preparing electrodes on the multi-layer lead-free piezoelectric ceramic sheet.
[0017] In the present invention, preparing external electrodes on multilayer lead-free piezoelectric ceramic sheets is preparing external electrodes or preparing external electrodes and internal electrodes. The external electrodes can be silver electrodes sintered outside the multilayer lead-free piezoelectric ceramic sheets, and the internal electrodes are silver-palladium electrodes.
[0018] The present invention further proposes a method for preparing a piezoelectric ceramic driving component using a multilayer lead-free piezoelectric ceramic sheet, which is characterized by comprising the following steps:
[0019] Step A: obtaining a lead-free piezoelectric ceramic green sheet by the method described in step 1;
[0020] Step B: Preparation of inner electrode:
[0021] Step B-1: First, silver-palladium electrode slurry is mixed with KNN ceramic powder, wherein type A KNN powder accounting for 10-20% of the total mass of the electrode slurry is added to the type A electrode slurry, and type B KNN powder accounting for 10-20% of the total mass of the electrode slurry is added to the type B electrode slurry to prepare the corresponding internal electrode slurry;
[0022] Step B-2: cutting the aged green body as required, printing the internal electrode slurry on the surface of the cut green body and marking it;
[0023] Step B-3: alternately stacking A-type piezoelectric ceramic green bodies and B-type piezoelectric ceramic green bodies of different components, and subjecting the stacked green bodies to a lamination isostatic pressing treatment at 30-50 MPa to obtain laminated green bodies;
[0024] Step B-4: After the laminated green blocks are separated by pattern punching, they are placed in a high-temperature sintering furnace for sintering to obtain sintered multi-layer lead-free ceramics;
[0025] Step B-5: grinding the end surface of the sintered multilayer ceramic to expose the internal electrode; Step C: preparing the external electrode, using a silver paste suitable for low-temperature sintering to print the end surface and the external electrode area respectively, and sintering at a low temperature of 500-600°C after drying to obtain a preform;
[0026] Step D: subjecting the preform to oil bath polarization treatment to obtain a finished product.
[0027] The polarization treatment described in the present invention is: placing in an oil bath at a temperature of 120° C. and polarizing in an electric field with a polarization field strength of 3 KV / mm for 5 minutes.
[0028] Compared with the prior art, the present invention solves the problem that the piezoelectric properties of existing KNN-based piezoelectric ceramic materials are greatly affected by factors such as temperature and humidity, which limits their application scope; by constructing room temperature polycrystalline phase coexistence, the piezoelectric properties are improved, and effective temperature control is performed to ensure that they have excellent piezoelectric properties at working temperature; the problems and challenges of existing lead-free piezoelectric ceramic materials in terms of cost, performance stability, etc. are solved. The process used is simple, the performance is stable, it is suitable for mass production, and it does not contain harmful lead elements and has good environmental friendliness. Description of the drawings:
[0029] Appendix 1 is a comparison of product performance of different solutions.
[0030] Attached Figure 1 This is a schematic diagram of the internal electrode pattern of type A green body printing.
[0031] Attached Figure 2 This is a schematic diagram of the internal electrode pattern printed on the B-type green body.
[0032] Attached Figure 3 It is a schematic diagram of three-layer alternating stacking of type A green sheets and type B green sheets.
[0033] Attached Figure 4 This is a schematic diagram of the printing and coating of external electrodes and end surface electrodes.
[0034] Attached Figure 5 This is the shrinkage curve of silver-palladium internal electrode with different proportions of KNN powder added.
[0035] Attached Figure 6 This is the cross-sectional SEM image of the silver-palladium electrode when it is not doped with KNN powder.
[0036] Attached Figure 7 This is a cross-sectional SEM image of the silver-palladium electrode doped with 20% KNN powder in the present invention.
[0037] Attached Figure 8 This is a SEM image of the silver-palladium electrode of the internal electrode of the three-layer product in an embodiment of the present invention.
[0038] Reference numerals: 1 green body, 2 internal silver-palladium electrode, 3 external electrode, 4 end surface electrode. Specific implementation method:
[0039] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0040] The present invention adopts O-phase high-purity niobium pentoxide, sodium carbonate, potassium carbonate and the like which are dehydrated at 300-400°C, ball-milled and mixed, and then pre-sintered. In the sodium potassium niobate system, two types of green bodies, A and B, are adopted to achieve doping and regulation with metal oxides such as lithium, tantalum, antimony, etc., so as to construct a multi-phase coexistence effect at room temperature or in its operating temperature range, and improve piezoelectricity.
[0041] Embodiment 1:
[0042] This example provides a method for preparing a multilayer lead-free KNN piezoelectric ceramic, which specifically includes the following steps:
[0043] Step (1): Take the raw materials according to the proportion and add them into the grinding tank, wherein the mass ratio of zirconium oxide grinding ball: anhydrous ethanol: raw material powder is 6:3:1, and the chemical formula of the raw material powder is x Na 0.52 K (1-x-0.52) Nb (1-y-z) Sb y Ta z O 3; , where x=4%, y=7.5%, and Z=5% in type A green powder; x=6%, y=10%, and Z=5% in type B green powder, i.e., the corresponding type A powder composition is: 0.04 Na 0.52 K 0.44 Nb 0.85 Sb 0.075 Ta 0.05 O3,
[0044] Corresponding to type B powder, the component is Li 0.06 Na 0.52 K 0.42 Nb 0.85 Sb 0.1 Ta 0.05 O3, the powder is prepared by weighing Li2CO3, Na2CO3, K2CO3, Nb2O5, Ta2O5, and Sb2O3 respectively and mixing them in proportion; step (2): using a planetary ball mill, mixing at 500 rpm for 24 hours, drying, grinding, and passing the mixed powder through a 100-mesh sieve;
[0045] Step (3): placing the two sieved powders in different alumina crucibles and pre-sintering them at a high temperature of 900° C. for 5 hours;
[0046] Step (4): adding 7% PVB as a binder, 2% triacetin as a plasticizer, 1% oleic acid as a dispersant and anhydrous ethanol as a solvent to the pre-sintered 1# and 2# powders to prepare a casting slurry with a solid content of 60%;
[0047] Step (5): placing the prepared slurry in a drum ball mill, and ball milling at a speed of 120 rpm for 18 hours, and placing the mixed slurry in an environment with a temperature of 23° C. and a humidity of 48% for 48 hours;
[0048] Step (6): placing the Type A and Type B slurries that have been left to stand in the silo of the coating machine respectively, coating them with a gap of 0.1 mm and a speed of 400 mm / min, and drying them at three drying temperatures of 40° C., 60° C., and 40° C.;
[0049] Step (7): Cut the dried type A and type B green sheets into 100*100 mm patterns respectively, and stack the cut type A and type B green sheets in three layers in a cross order, i.e. type A, type B, type A, and so on, and place the stacked green sheets in an isostatic pressing device and stack them at a pressure of 20 MPa for 5 min;
[0050] Step (8): placing the laminated green body in a box-type sintering furnace and keeping it at 600° C. for 3 hours for debinding, and keeping it at 1100° C. for 3 hours for sintering;
[0051] Step (9): The sintered piezoelectric ceramic is subjected to polarization treatment to obtain a piezoelectric ceramic product, specifically, the piezoelectric ceramic is placed in an oil bath at a temperature of 120° C. and polarized in an electric field with a polarization field strength of 3 KV / mm for 5 minutes.
[0052] This example further provides an application of the multilayer lead-free piezoelectric ceramic sheet of this example, specifically a piezoelectric ceramic sheet as
[0053] Step (10): After polishing and removing the passivation layers on the upper and lower surfaces of the sintered piezoelectric ceramic, printing external silver electrodes, and sintering with silver at 600° C. for 10 min;
[0054] Step (11): The silvered piezoelectric ceramic is placed at room temperature for 24 hours and then its piezoelectric properties are tested.
[0055] In this example, two types of green billets, A and B, are used to achieve doping control with metal oxides such as lithium, tantalum, and antimony, thereby constructing a multi-phase coexistence effect at room temperature or its operating temperature range and improving piezoelectricity. In order to verify this advantage of this example, comparative examples 1 and 2 are set up, wherein comparative example 1 is made by stacking type A green billets, and comparative example 2 is made by stacking type B green billets. As shown in Table 1, compared with comparative examples 1 and 2, the KNN piezoelectric ceramics prepared in this example have d33 of approximately 340pC / N and Kp of approximately 48%, and have excellent piezoelectric properties.
[0056] Embodiment 2:
[0057] This example provides another application of the multilayer lead-free piezoelectric ceramic sheet obtained in Example 1. The preparation of the green body in this example is as described in Example 1, and type A and type B green bodies are prepared. The relevant powders and green body production processes are the same and will not be repeated.
[0058] This example further prepared the internal electrodes, including:
[0059] S1: Printing internal electrode slurry on the surface of type A and type B green body respectively, wherein the internal electrode slurry is silver-palladium slurry prepared by co-precipitation powder or alloy powder, the silver-palladium mixing ratio is 70 / 30, and type A powder and type B powder prepared by the above-mentioned solid phase method are added, and the addition ratio is 20% of the total mass, wherein the internal electrode slurry corresponding to the type A green body is added with type A powder accounting for 20% of the total amount of electrode slurry, and the internal electrode slurry corresponding to the type B green body is added with type B powder accounting for 20% of the total amount of electrode slurry, thereby preparing internal electrode slurry matching the shrinkage rate of the green body; S2: Using the above-mentioned internal electrode slurry to print patterns on the surface of the green body respectively, as shown in the attached Figure 1 and attached Figure 2 As shown in FIG. 1 , the surface of the green body after printing has an external electrode 3, and has an end surface electrode 4 located on the side of the green body connected to the external electrode 3. In this example, the end surface electrode 4 and the external electrode 3 are both fired with the internal electrode slurry, and the end surface electrode 4 can also be a silver electrode; then the A-type and B-type green bodies after printing are cross-stacked in three layers, as shown in FIG. Figure 3 As shown, after stacking, the external electrodes 3 on the A-type green body and the B-type green body are partially overlapped, and the end surface electrodes 4 are placed opposite to each other; the stacked green body is placed in an isostatic pressing device, and is pressurized at 30 MPa for 5 minutes. The isostatically pressed green body is punched into a single pattern using a related mold;
[0060] S3: Place the cut patterns in an alumina crucible in sequence, suspend a cover plate 5 times the weight of the green body above the green body, support the cover plate with a 900℃ decomposable carbon tape around the cover plate, place the alumina crucible with the green body in a box-type sintering furnace, and perform low-temperature debonding at 600℃ for 5 hours; the second high temperature is kept at 900℃ for 1 hour, and the high temperature is kept at 1100℃ for 3 hours. When the temperature rises to 900℃, the green body begins to sinter into porcelain, which has a certain strength at this time. The carbon tape begins to slowly decompose, and the cover plate slowly falls, thereby effectively suppressing defects such as warping and deformation caused by inconsistent thermal stress during high-temperature sintering;
[0061] S4: polishing the surface passivation layer of the sintered multilayer piezoelectric ceramic: using a 10000# alumina sanding belt to polish the two end surfaces of the ceramic containing the internal electrode area respectively until the internal electrode can be observed under a microscope;
[0062] S5: Print the low-temperature sintered silver paste on the upper and lower surfaces and the two side end faces of the piezoelectric ceramic by screen printing or coating, respectively, to ensure the conduction of the relevant internal circuits; it is necessary to ensure that the upper and lower surface patterns are connected to the silver films of the two side end face patterns;
[0063] S6: The multilayer piezoelectric ceramics with printed external electrodes are placed in a mesh belt sintering furnace and sintered at 600°C for 10 minutes. In order to effectively reduce the degradation of piezoelectric performance caused by silver film sintering, a low-temperature and rapid sintering method is used;
[0064] S7: The multilayer piezoelectric ceramics sintered with silver are placed in a silicone oil bath, and polarized at an oil bath temperature of 120°C, a polarization voltage of 0.6KV, and a polarization time of 10min. The polarized piezoelectric ceramics are placed at room temperature for natural aging, and relevant performance tests are performed after aging for 24 hours.
[0065] As shown in Table 1, the electrostatic capacitance of the piezoelectric ceramic prepared in this embodiment can be increased to 8.5 times that of a single-plate piezoelectric ceramic of the same specification, and Kp is about 43%. It can be driven at low voltage and respond quickly, and can be widely used in various precision components such as actuators.
[0066] Table 1 Performance analysis of each embodiment of the present invention
[0067]
[0068]
[0069] The present invention adopts a ball milling process to prepare nano powder with concentrated particle size distribution, so that the powder has excellent activity, thereby reducing the sintering temperature; the solid phase synthesis method is used to prepare KNN powder, which has low dependence on equipment and can be produced in batches stably, and then the casting method is used to prepare blank films with different components, and the isostatic pressing equipment is used to stack them at a pressure of 20-30MPa, thereby constructing the coexistence of polycrystalline phases within a certain temperature range and improving the piezoelectric performance; in addition, the internal electrode of the piezoelectric ceramic device prepared by the present invention is prepared by adding a certain proportion of ceramic powder to silver palladium slurry, so as to match its shrinkage rate, such as Figure 5 As shown in the figure, if KNN powder is not doped, the shrinkage rate of the silver-palladium paste increases significantly due to the rapid combustion of organic matter in the temperature range of 500-600℃, resulting in mismatched shrinkage in some areas, causing poor continuity of the internal electrodes, open circuits in some areas, and poor performance, such as Figure 6 As shown in the figure; after doping with 10% KNN powder, when the internal electrode is co-fired with the KNN blank film, due to the addition of the same KNN material, its shrinkage rate becomes gentle with temperature changes, thereby suppressing local disconnection and open circuit caused by a sudden increase in shrinkage rate, as shown in the figure. Figure 7 , 8The internal electrodes shown are neat and continuous, thereby increasing the coverage of the entire electrode film surface and improving the relevant performance of piezoelectric ceramics. If the KNN powder addition content reaches 30%, the viscosity of the silver-palladium electrode slurry increases rapidly, generally from 50-60Pa.s to more than 120Pa.s; which leads to easy sticking to the screen or poor uniformity of the film surface during printing, resulting in poor conductivity and reduced product performance. The present invention also adopts a two-stage high-temperature sintering process to effectively control the particle growth size, thereby suppressing the defects and performance degradation caused by large particle size production. Effective temperature control is performed on piezoelectric ceramics to ensure that they have excellent piezoelectric properties at the operating temperature, so as to avoid performance degradation caused by the volatilization of components deviating from the stoichiometric ratio during sintering.
Claims
1. A method for preparing a multilayer lead-free piezoelectric ceramic sheet, characterized in that: The method is obtained by isostatic pressing of two different types of sheets, type A and type B, in an alternating manner, and specifically includes the following steps: Step 1: Prepare type A and type B piezoelectric ceramic green bodies respectively: Step 1-1: Weigh the piezoelectric ceramic green powder, the chemical formula of which is li x Na 0.52 K (1-x-0.52) Nb (1-y-z) Sb y Ta z O 3; , where x=4%, y=7.5%, Z=5% in A-type piezoelectric ceramic green powder, and the chemical formula is li 0.04 Na 0.52 K 0.44 Nb 0.85 Sb 0.07 5Ta 0.05 O3, B-type piezoelectric ceramic green powder contains x=6%, y=10%, Z=5%, and the chemical formula is Li 0.06 Na 0.52 K 0.42 Nb 0.8 5Sb 0.1 Ta 0.05 O3 is prepared by weighing Li2CO3, Na2CO3, K2CO3, Nb2O5, Ta2O5 and Sb2O3 respectively and mixing them, wherein sodium carbonate and potassium carbonate powders are dried and dehydrated at 300-400°C in advance; Step 1-2: Add the weighed powders to the ball mill respectively, and add grinding balls, grinding media, and powder raw materials respectively, place the raw materials in a planetary ball mill or a nano ball mill for powder grinding, mix them thoroughly, and ball mill at 400-500rpm for 24-36 hours; Step 1-3: The ball-milled slurry is sieved to separate the balls, the separated slurry is desolventized and dried, and the dried powder is ground and dispersed using a mortar grinder to form powder accumulation particles with uniform particle size and no agglomeration; Step 1-4: placing the powder stacked particles in an alumina crucible and pre-sintering at 900-950° C.; Step 1-5: The pre-sintered powder is placed in a ball mill, and plasticizer, solvent, dispersant, and PVB are added respectively. The powder is ball milled at 100-150 rpm for 18 hours using a drum ball mill. After that, the slurry is left to stand for 48 hours for full emulsification and dispersion. Step 1-6: The emulsified and dispersed slurry is subjected to degassing treatment, and the degassing slurry is placed in a coating machine to be made into 30-50 μm thick type A piezoelectric ceramic green bodies and type B piezoelectric ceramic green bodies, respectively, and placed in a constant temperature and humidity chamber for aging; Step 2: alternately stacking the aged type A piezoelectric ceramic green bodies and the type B piezoelectric ceramic green bodies to form stacked green bodies, and performing a 30-50 MPa lamination isostatic pressing treatment on the stacked green bodies to obtain isostatically pressed green bodies; Step 3: placing the isostatically pressed green block in a high-temperature sintering furnace for sintering; Step 4: The sintered piezoelectric ceramics are polarized to obtain a multi-layer lead-free piezoelectric ceramic sheet.
2. An application of a piezoelectric ceramic sheet obtained by the method for preparing a multi-layer lead-free piezoelectric ceramic sheet as claimed in claim 1, characterized in that: A piezoelectric ceramic driving component is prepared using a multilayer lead-free piezoelectric ceramic sheet. Specifically, electrodes are prepared on the multilayer lead-free piezoelectric ceramic sheet. The external electrode is prepared on the multilayer lead-free piezoelectric ceramic sheet, which is an external electrode or an external electrode and an internal electrode. The external electrode is a silver electrode sintered on the outside of the multilayer lead-free piezoelectric ceramic sheet, and the internal electrode is a silver-palladium electrode.
3. An application of a piezoelectric ceramic sheet obtained by the method for preparing a multi-layer lead-free piezoelectric ceramic sheet as claimed in claim 1, characterized in that: The following steps are involved: Step A: obtaining a lead-free piezoelectric ceramic green sheet by the method described in step 1; Step B: Preparation of inner electrode: Step B-1: First, silver-palladium electrode slurry is mixed with KNN ceramic powder, wherein type A KNN powder accounting for 10-20% of the total mass of the electrode slurry is added to the type A electrode slurry, and type B KNN powder accounting for 10-20% of the total mass of the electrode slurry is added to the type B electrode slurry to prepare the corresponding internal electrode slurry; Step B-2: cutting the aged green body as required, printing the internal electrode slurry on the surface of the cut green body and marking it; Step B-3: alternately stacking A-type piezoelectric ceramic green bodies and B-type piezoelectric ceramic green bodies of different components, and subjecting the stacked green bodies to a lamination isostatic pressing treatment at 30-50 MPa to obtain laminated green bodies; Step B-4: After the laminated green blocks are separated by pattern punching, they are placed in a high-temperature sintering furnace for sintering to obtain sintered multi-layer lead-free ceramics; Step B-5: grinding the end surface of the sintered multilayer ceramic to expose the internal electrode; Step C: preparing the external electrode, using a silver paste suitable for low-temperature sintering to print the end surface and the external electrode area respectively, and sintering at a low temperature of 500-600°C after drying to obtain a preform; Step D: subjecting the preform to oil bath polarization treatment to obtain a finished product.